Too Much Pay-Performance Sensitivity? - Brick, Ivan E.; Palmon, Oded; Wald, John K. (The Review of Economics and Statistics, 2012)
We examine the relation between pay-performance sensitivity (PPS), the convexity of managerial compensation (Vega), and future stock risk and returns for a large sample of firms between 1992 and 2004. Higher PPS and Vega are both associated with lower future stock returns. Part of this negative relation can be explained by risk-averse managers decreasing equity risk in response to increases in PPS and Vega. However, even after correcting for lower future risk, future stock returns are negatively associated with the magnitude of option sensitivity. This finding is consistent with previous studies that link high option compensation to manager-owner agency problems.